Percepcija slovenskih sredinskih samoglasnikov pri študentih na Obali - Volk, Jana (Jezik in slovstvo, 2018)
The article presents the results of tests of hearing detection and recognition of medial vowels. Students of various study programmes at the Faculty of Humanities of the University of Primorska participated in the perception test. The results acquired were compared to two studies carried out among students of Slovenian and Slavic studies in Ljubljana (Tivadar 2004) and among high school students in the Pomurje region (Huber 2006). The data obtained with the perception test were analysed according to the criteria of study programme, dialect group and gender. It was determined that students in the Slovenian Littoral have weaker abilities to recognise medial vowel quality compared to students in Ljubljana and Pomurje. The best results were observed among students of Slovenian studies and among female participants.
Keywords: fonetika; Obala; perceptivni testi; samoglasniki; slovenščina